The Psychological Adjustment of Recent Crime Victims in the Criminal Justice System - Freedy, John R. (Journal of interpersonal violence, 1994)
The goals of this investigation were to examine the prevalence of Post-Traumatic Stress Disorder (PTSD) and victim service utilization among crime victims and family members recently involved in the criminal justice system ( N = 251). About one half of the participants met PTSD diagnostic criteria during their lifetime. Females were overrepresented in the more violent crimes (e.g., homicide and sexual assault). Victims of more violent crimes-who sustained physical injuries, who perceived that they would be seriously injured, and who perceived their lives were threatened-were more likely to suffer from PTSD than victims who did not have these characteristics. Most participants believed the criminal justice system should provide a range of victim services. However, most participants reported inadequate access to services. Also, receipt of psychological counseling and diagnostic status were significantly associated with crime type. Results imply that crime victims involved in the criminal justice system are at risk for developing PTSD, which often never is addressed by a mental health professional due to inadequate access to health care services